ZTA ceramic and preparation method thereof

ZTA ceramics were prepared by mechanical mixing, and a tetragonal phase ZrO2 crystal structure was formed using wet ball milling and sintering technology, which solved the problem of high brittleness of Al2O3 ceramics, achieving performance improvement and cost reduction.

CN119462088APending Publication Date: 2025-02-18SUZHOU ROUTAO NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411547585.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Al2O3 ceramics have microscopic defects in the production process, resulting in high brittleness, and the prior art is difficult to effectively improve their fracture toughness.

Method used

The Al2O3 powder and ZrO2 grinding balls were wet ball milled by mechanical mixing to prepare ZTA powder with a ZrO2 content between 1 and 10 wt%, and a stable tetragonal phase ZrO2 in-crystal structure was obtained through sintering to achieve toughening.

Benefits of technology

This method can improve the bending strength, fracture toughness and hardness of Al2O3 ceramics, reduce costs, and be suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462088A_ABST
    Figure CN119462088A_ABST
Patent Text Reader

Abstract

The invention discloses ZTA ceramic and a preparation method thereof, and belongs to the technical field of inorganic material preparation. The preparation method of the ZTA ceramic comprises the following steps: S1, placing Al2O3 powder and ZrO2 grinding balls in ball milling equipment, adding ultrapure water as a ball milling medium liquid, adding an organic binder, and carrying out wet ball milling to obtain ZTA slurry with the ZrO2 content of 1-10 wt%; s2, sieving the ZTA slurry, and carrying out cold isostatic pressing on a screen underflow to obtain a ZTA green body; and S3, calcining the ZTA green body to remove the organic binder, and sintering to obtain the ZTA ceramic. According to the invention, the ZTA powder is prepared by a mechanical mixing method under the condition of not additionally adding ZrO2 powder and a stabilizer, and a stable tetragonal phase ZrO2 intragranular structure is obtained after sintering, so that toughening is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technology in the field of inorganic material preparation, in particular to a ZTA ceramic and a preparation method thereof. Background Art

[0002] The flexural strength of Al2O3 ceramics is 200-600MPa and the fracture toughness is 2-5MPa·m 1 / 2 , Vickers hardness is 1200 ~ 2000HV, it is an important engineering material, widely used in machinery, chemical industry, electronics, medical and other fields. However, in the production process, the influence of various factors leads to some microscopic defects in its crystal structure. When subjected to external stress and stress concentration, microcracks are easily generated, and microcracks will expand rapidly, causing Al2O3 ceramics to show significant high brittleness.

[0003] In order to change this situation, researchers have been looking for simple and effective methods to improve the fracture toughness of Al2O3 ceramics. The current mainstream solution is to introduce toughening phase materials into Al2O3 ceramics. Commonly used toughening phase materials include particles, whiskers, short fibers, continuous fibers and carbon-based materials. Compared with Al2O3 ceramics, ZrO2 ceramics have higher fracture toughness and bending strength. Dispersing nano ZrO2 as a second phase in the Al2O3 ceramic matrix can obtain zirconium oxide toughened alumina (ZTA) ceramics, which improves the high brittleness of Al2O3 ceramics.

[0004] The preparation of ZTA powder materials includes mechanical mixing, coprecipitation, sol-gel and hydrothermal synthesis. The mechanical mixing method is to mix ZrO2 powder and Al2O3 powder and then perform ball milling. It does not require complex chemical reagents and harsh reaction conditions, so the cost is relatively low. Although the mechanical mixing method can achieve the mixing of ZrO2 powder and Al2O3 powder, it is difficult to ensure the uniform dispersion of multiphase components due to the differences in physical properties between particles (such as particle size, shape, density, etc.); if the dispersion is uneven, it will lead to problems such as high porosity and decreased mechanical properties in the prepared ZTA ceramic material.

[0005] In order to solve the above problems in the prior art, the present invention is provided. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a ZTA ceramic and a preparation method thereof. Without adding additional ZrO2 powder and stabilizer, ZTA powder is prepared by a mechanical mixing method, and a stable tetragonal ZrO2 intracrystalline structure is obtained after sintering to achieve toughening.

[0007] The first aspect of the present invention relates to a method for preparing a ZTA ceramic, comprising the following steps:

[0008] S1, placing Al2O3 powder and ZrO2 grinding balls in a ball mill, adding ultrapure water as a ball milling medium, and adding an organic binder to perform wet ball milling; after the ball milling is completed, taking out the ball milling slurry and drying it to obtain ZTA powder with a ZrO2 content between 1 and 10wt%;

[0009] S2, sieving the ZTA powder, taking the material under the sieve and performing cold isostatic pressing to obtain a ZTA green body;

[0010] S3, calcining the ZTA green body to remove the organic binder, and then sintering to obtain the ZTA ceramic;

[0011] In step S1, the weight ratio of the Al2O3 powder and the ZrO2 grinding balls is (5-10):1;

[0012] The ZrO2 grinding balls include: 1 part by weight of ZrO2 grinding balls with a diameter of 5 mm, 1 to 2 parts by weight of ZrO2 grinding balls with a diameter of 10 mm, and 1 to 2 parts by weight of ZrO2 grinding balls with a diameter of 15 mm.

[0013] For some specific implementation schemes, the weight ratio of Al2O3 powder and ZrO2 grinding balls can be 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.

[0014] For some specific implementation schemes, ZrO2 grinding balls with diameters of 5 mm, 10 mm, and 15 mm can be used in the following weight ratios: 1:1:1, 1:1:2, 1:2:1, or 1:2:2, etc.

[0015] Preferably, the average particle size of the Al2O3 powder is 30 to 100 nm; for example, the average particle size may be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.

[0016] For some specific implementation schemes, the ball milling speed in the wet ball milling is 200-300 r / min, for example, the ball milling speed can be 200 r / min, 210 r / min, 220 r / min, 230 r / min, 250 r / min, 270 r / min, 280 r / min, 300 r / min, etc.

[0017] For some specific embodiments, the organic binder is at least one of polyvinyl alcohol, polyurethane, polyacrylate and resin adhesive, and the added amount is 1% to 6% of the weight of Al2O3 powder; for example, the added amount can be 1%, 2%, 3%, 4%, 5%, 6%, etc.

[0018] For some specific implementation schemes, in the step S1, the ball-milled slurry is dried at 100-200°C for 1 hour to obtain ZTA powder; for example, the drying temperature can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.

[0019] For some specific embodiments, the ZrO2 content in the ZTA powder can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc.

[0020] For some specific embodiments, the average particle size of the undersize is 30 to 100 nm; for example, the average particle size may be 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.

[0021] For some specific implementation schemes, the pressure in the cold isostatic pressing is 100-300 MPa; for example, the pressure is 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, etc.

[0022] For some specific embodiments, the calcination temperature in the calcination treatment is 500-600°C, the calcination time is 60-120 min, and the heating rate is 5-10°C / min; for example, the calcination temperature is 500°C, 520°C, 550°C, 560°C, 590°C, 600°C, etc., the calcination time is 60min, 70min, 80min, 90min, 100min, 110min, 120min, etc., and the heating rate is 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc.

[0023] For some specific implementation schemes, the sintering temperature in the sintering treatment is 1200-1800°C, the sintering time is 30-60 min, and the heating rate is 10-20°C / min; for example, the sintering temperature is 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, etc., the calcination time is 30min, 40min, 50min, 60min, etc., and the heating rate is 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min, etc.

[0024] A second aspect of the present invention relates to a ZTA ceramic, which is made by the above-mentioned preparation method.

[0025] Compared with the prior art, the present invention has the following technical effects:

[0026] 1) The present invention places Al2O3 powder and ZrO2 grinding balls of different diameters into a ball mill for wet ball milling. During the ball milling process, the Al2O3 powder cuts the ZrO2 grinding balls, and the grinding balls collide with each other, resulting in wear of the grinding balls. However, the ZrO2 grinding powder and stabilizer powder obtained by wear and tear on the grinding balls will be wrapped in the surrounding Al2O3 powder, and after sintering, a large amount of intracrystalline structure (second phase particles ZrO2 are embedded in the matrix particles Al2O3) is formed, which is dispersed in the Al2O3 ceramic matrix, wherein the ZrO2 particles are tetragonal and stabilized by the stabilizer; the existence of the intracrystalline structure causes subgrain boundaries to appear inside the Al2O3 particles, achieving the effect of fine particle strengthening, and the dislocations of the Al2O3 particles are pinned by the intracrystalline structure ZrO2 particles, thereby increasing the resistance to dislocation movement and deformation resistance, making it difficult to continue deformation, thereby improving the strength;

[0027] 2) The preparation process of the method of the present invention is simple, easy to operate and implement, and does not require the addition of additional ZrO2 powder and stabilizer; compared with other preparation methods such as chemical methods, the mechanical mixing method does not require complex chemical reagents and harsh reaction conditions, so the cost is relatively low, and it is easy to realize industrial production, which can meet the needs of large-scale preparation of ZTA powder materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a SEM photo of the ZTA ceramic in Example 2;

[0029] Figure 2 is a SEM photograph of the ZTA ceramic in Comparative Example 1;

[0030] Figure 3 This is the XRD diffraction pattern of the ZTA powder in Example 2. DETAILED DESCRIPTION

[0031] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The experimental methods without specific conditions in the examples are carried out according to conventional methods and conditions.

[0032] Source of raw materials

[0033] ZrO2 grinding balls (purity not less than 99.99%), Al2O3 powder (purity not less than 99.99%) and organic binder are all commercially available raw materials, and ultrapure water is produced by ultrapure water equipment.

[0034] Test Method

[0035] 1. Microstructure

[0036] Test method: Refer to "EN 623-3: 1993 Advanced technical ceramics-Monolithic ceramics General and textural properties-Part 3: Determination of grain size and size distribution (characterized by the Linear Intercept Method)" and use Zeiss scanning electron microscope to take morphological photos.

[0037] 2. Mechanical properties testing

[0038] Flexural strength: The test method refers to "IS0 14704 Fine ceramics (advanced ceramics, advanced technical ceramics)-Test method for flexural strength of monolithicceramics at room temperature". The results are shown in Table 1.

[0039] Fracture toughness: The test method refers to ISO 23146 Fine ceramics (advanced ceramics, advanced technical ceramics)-Test methods for fracture toughness of monolithic ceramics-Single-edge V-notch beam (SEVNB) method. The results are shown in Table 1.

[0040] Hardness: The test method refers to ISO 14705 Fine ceramics (advanced ceramics, advanced technical ceramics) - Test method for hardness of monolithic ceramics at room temperature. The results are shown in Table 1.

[0041] Example 1

[0042] The process of preparing ZTA ceramics in this embodiment is as follows.

[0043] S1, placing Al2O3 powder with an average particle size of 50nm and ZrO2 grinding balls in a ball mill at a weight ratio of 10:1; the ZrO2 grinding balls are three types of ZrO2 grinding balls with diameters of 5mm, 10mm and 15mm and a weight ratio of 1:1:1; adding ultrapure water as the ball milling medium liquid, and adding organic binder PVA at 1% of the weight of the Al2O3 powder; setting the ball milling speed to 300r / min, controlling the ball milling time to 30min, and preparing ZTA powder with a ZrO2 content of 1wt%;

[0044] S2, sieving the ZTA powder to obtain the undersize with an average particle size of 50 nm, and cold isostatic pressing the undersize with a pressure of 220 MPa to obtain a ZTA green body;

[0045] S3, placing the ZTA green body in a calcining furnace, heating it to 200°C at a heating rate of 10°C / min, calcining it for 60 minutes to remove the organic binder; then placing it in a sintering furnace, heating it to 1600°C at a heating rate of 10°C / min, sintering it for 40 minutes to obtain ZTA ceramics.

[0046] Example 2

[0047] Compared with Example 1, the difference of this embodiment is that the ball milling time is controlled to 60 minutes, and the ZTA powder with a ZrO2 content of 3 wt% is obtained in step S1.

[0048] Example 3

[0049] Compared with Example 1, the difference of this embodiment is that the ball milling time is controlled to 100 min, and the ZTA powder with a ZrO2 content of 5 wt% is obtained in step S1.

[0050] Example 4

[0051] Compared with Example 1, the difference of this embodiment is that the ball milling time is controlled to be 140 minutes, and the ZTA powder with a ZrO2 content of 7 wt% is obtained in step S1.

[0052] Comparative Example 1

[0053] Compared with Example 1, the difference of this embodiment is that Al2O3 powder and ZrO2 powder are added in a weight ratio of 97:3, and agate balls with a diameter of 10 mm are used as grinding balls. Step S1 produces ZTA powder with a ZrO2 content of 3wt%.

[0054] Examples 1 to 4 and Comparative Example 1 were tested, and the test results are shown in Table 1.

[0055] Table 1 Test results project Flexural strength (MPa) <![CDATA[Fracture toughness (MPa·m 1 / 2 ).]]> Hardness (GPa) Example 1 785.82 4.77 16.83 Example 2 1322.90 8.49 21.32 Example 3 1072.21 6.83 17.26 Example 4 975.90 5.65 17.03 Comparative Example 1 737.42 4.31 16.72

[0056] Figure 3 The XRD diffraction pattern shows that the zirconium oxide in the prepared ZTA powder is mainly tetragonal phase;

[0057] Compare again Figure 1 and Figure 2 It can be found that in Example 2, ZrO2 forms a large number of intracrystalline structures after sintering, and is encapsulated in Al2O3 as a second phase and is dispersed; and because of the presence of the stabilizer, ZrO2 is a stable tetragonal phase; while in Comparative Example 1, ZrO2 powder (monoclinic phase at room temperature) is directly mechanically mixed with Al2O3 powder, and the particle size and distribution of ZrO2 are uneven, with a larger size and mainly distributed at the grain boundaries;

[0058] Next, by comparing the test results of Example 2 and Comparative Example 1, it can be found that the larger ZrO2 in Comparative Example 2 is mainly distributed at the grain boundaries, and the toughening effect is limited; while the ZrO2 in the ZTA ceramic prepared by the method of the present invention is in a stable tetragonal phase and dispersedly distributed, and has a relatively strong toughening and strengthening effect, and the flexural strength, fracture toughness and Vickers hardness reach 1322.90MPa and 8.49MPa·m, respectively. 1 / 2 , 21.32 Gpa, which are 44.25%, 49.23% and 21.57% higher than those of ZTA ceramics prepared by traditional methods. It can be considered that the existence of intracrystalline structure makes subgrain boundaries appear inside Al2O3 particles, which is similar to the re-refinement of structure, achieving the effect of fine particle strengthening. The dislocations of Al2O3 particles will be pinned by the stable intracrystalline structure t-ZrO2 particles, thereby increasing the resistance to dislocation movement, increasing the deformation resistance, making it difficult to continue deformation, and thus improving the above-mentioned performance.

[0059] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing ZTA ceramics, characterized in that: The following steps are involved: S1, placing Al2O3 powder and ZrO2 grinding balls in a ball mill, adding ultrapure water as a ball milling medium, and adding an organic binder to perform wet ball milling; after the ball milling is completed, taking out the ball milling slurry and drying it to obtain ZTA powder with a ZrO2 content between 1 and 10wt%; S2, sieving the ZTA powder, taking the material under the sieve and performing cold isostatic pressing to obtain a ZTA green body; S3, calcining the ZTA green body to remove the organic binder, and then sintering to obtain the ZTA ceramic; In step S1, the weight ratio of the Al2O3 powder and the ZrO2 grinding balls is (5-10):1; The ZrO2 grinding balls include: 1 part by weight of ZrO2 grinding balls with a diameter of 5 mm, 1 to 2 parts by weight of ZrO2 grinding balls with a diameter of 10 mm, and 1 to 2 parts by weight of ZrO2 grinding balls with a diameter of 15 mm.

2. The method for preparing ZTA ceramics according to claim 1, characterized in that: The average particle size of the Al2O3 powder is 30 to 100 nm.

3. The method for preparing ZTA ceramics according to claim 2, characterized in that: The ball milling speed in the wet ball milling is 200-300 r / min.

4. The method for preparing ZTA ceramics according to claim 3, characterized in that: The organic binder is at least one of polyvinyl alcohol, polyurethane, polyacrylate and resin adhesive, and the added amount is 1% to 6% of the weight of the Al2O3 powder.

5. The method for preparing ZTA ceramics according to claim 4, characterized in that: In the step S1, the ball-milled slurry is dried at 100-200° C. for 1 hour to obtain ZTA powder.

6. The method for preparing ZTA ceramics according to claim 5, characterized in that: The average particle size of the undersize material is 30 to 100 nm.

7. The method for preparing ZTA ceramics according to claim 6, characterized in that: The pressure during the cold isostatic pressing is 100-300 MPa.

8. The method for preparing ZTA ceramics according to claim 7, characterized in that: In the calcination treatment, the calcination temperature is 500-600° C., the calcination time is 60-120 min, and the heating rate is 5-10° C. / min.

9. The method for preparing ZTA ceramics according to claim 8, characterized in that: In the sintering process, the sintering temperature is 1200-1800° C., the sintering time is 30-60 min, and the heating rate is 10-20° C. / min.

10. A ZTA ceramic, characterized in that: The invention is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of high-hardness fine-grain ZTA system multiphase ceramic material

    CN114031376A

  • Preparation method of nano-zirconia toughened nano-alumina ceramic

    CN117383914A

  • Grain-grade zirconia toughened alumina ceramic substrate and method for preparing the same

    US20220402821A1